2004
DOI: 10.1021/cg030046e
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth Mechanism in a Solution of Hollow Whiskers of Molecular Compounds

Abstract: Hollow and solid whiskers are formed during the solvent exchange from the dimethyl sulfoxide or dimethylformamide solvates of dexamethasone acetate to the sesquihydrate by immersion of the initial phase in water. Detailed investigations using mainly optical and scanning electron microscopies lead us to propose a growth mechanism of the hollow whiskers. Six criteria appear to be necessary for the formation of thin tubular crystals during the solvent exchange. To reproduce the crystallization occurring at the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…After the observation in literature that crystalline hollow needles can be produced from many crystalline substances [2,3,5,6] and the demonstration of a case in which the ends of those needles can be closed [1], it was shown here that the hollow (this was again verified by an indirect method), closed needles could also be filled. It was demonstrated by two indirect methods that substances can be enclosed inside the needles, i.e., by the use of a fluorescence dye and the detection of a pharmaceutically active agent using UV spectroscopy.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…After the observation in literature that crystalline hollow needles can be produced from many crystalline substances [2,3,5,6] and the demonstration of a case in which the ends of those needles can be closed [1], it was shown here that the hollow (this was again verified by an indirect method), closed needles could also be filled. It was demonstrated by two indirect methods that substances can be enclosed inside the needles, i.e., by the use of a fluorescence dye and the detection of a pharmaceutically active agent using UV spectroscopy.…”
Section: Discussionmentioning
confidence: 56%
“…By changing the thermodynamic conditions, e.g., temperature, pressure or concentration (solvent), a phase transformation of solvates can be seen to occur [1][2][3], e.g., a monohydrate crystal immerged into an organic solvent in which the anhydrate represents the thermodynamically stable form. During solvent mediated phase transformation [4], the crystal water is transferred into the organic solvent due to the higher affinity of the incorporated water to the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors [28][29][30][31][32][33] have reported solvent-mediated phase transitions between different crystalline phases of a given material that result in the formation of hollow needles emanating from the original crystal (see Fig. 9).…”
Section: Example 4: Phase Transitions For Product Design -Generating mentioning
confidence: 99%
“…The resulting phase is generally the desolvated phase; in other words, and in the specific case of a crystal hydrate as starting material, the resulting phase is the anhydrate. One notable exception is the formation of hollow needles by solvent exchange as observed for dexamethasone acetate [32,33]. Although the presence of the anti-solvent is not a necessary condition for the transition to a desolvated phase, it is required for the formation of the hollow needles.…”
Section: Example 4: Phase Transitions For Product Design -Generating mentioning
confidence: 99%
“…For example, an ethanolic saturated solution of DMA injected in water (anti-solvent) [1] leads to the formation of hollow needlelike crystals called whiskers. At present, the mechanism of formation of these "whiskers" remains not fully understood [1,2]. In order to understand the mechanism of crystallization, it was first decided to characterize the solid phases of DMA in water.…”
Section: Introductionmentioning
confidence: 99%